2018
DOI: 10.1177/1056492618790920
|View full text |Cite
|
Sign up to set email alerts
|

The Serious and the Mundane: Reflections on Gamified CSR Communication

Abstract: We debate the strategic application of game elements to corporate messaging regarding societal and ecological concerns. We propose that gamified corporate social responsibility (CSR) communication is potentially well suited to create attention and involvement for corporate CSR initiatives. However, we argue that many gamification applications undermine their purpose and increase stakeholder suspicions about CSR. By debating the potential benefits and risks of gamified CSR communication, we aim to open the scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…It has also been suggested that digitalization promotes an illusory sense of resistance that counteracts genuine forms of resistance (e.g., Ossewaarde and Reijers, 2017), and that it has contributed to a whole range of new workplace conflicts (e.g., Upchurch and Grassman, 2016). Rather than applying digital technologies for positive social and organizational transformation, the organizational use of these technologies is often driven by instrumental profit concerns (e.g., Trittin et al, 2019). The basic idea is that the digitalization of organizations and organizing processes appears as a threat and harm to liberal and democratic citizenship rights (Matten and Crane, 2005; Vaidhyanathan, 2018).…”
Section: The Dark Sides Of Digitalization Of and For Organizations mentioning
confidence: 99%
“…It has also been suggested that digitalization promotes an illusory sense of resistance that counteracts genuine forms of resistance (e.g., Ossewaarde and Reijers, 2017), and that it has contributed to a whole range of new workplace conflicts (e.g., Upchurch and Grassman, 2016). Rather than applying digital technologies for positive social and organizational transformation, the organizational use of these technologies is often driven by instrumental profit concerns (e.g., Trittin et al, 2019). The basic idea is that the digitalization of organizations and organizing processes appears as a threat and harm to liberal and democratic citizenship rights (Matten and Crane, 2005; Vaidhyanathan, 2018).…”
Section: The Dark Sides Of Digitalization Of and For Organizations mentioning
confidence: 99%
“…Although the first documented use of the concept of gamification was in the early parts of this millennium (Dale, 2014; Kapp, 2012), gaming principles have been used for a long time – for example, in the military (Dicheva et al ., 2015). Gamification has gone from being a buzzword to denoting a popular way of thinking, and it is implemented to improve production (Warmelink et al ., 2018), improve communication with stakeholders (Trittin et al ., 2019), provide better conditions for training (Armstrong and Landers, 2018), enhance education (Bevins and Howard, 2018; Dicheva et al ., 2015) and even improve people’s health (see Korn and Schmidt, 2015 who also provide a good overview of the uptake of the concept). Gamification is also an important design principle in the contemporary capitalism of the “interface economy”, incorporated in algorithms in a variety of Web-based services such as Uber, Airbnb and so on (Finn, 2018).…”
Section: Gamification: Definition Roots and Applicationsmentioning
confidence: 99%
“…By seemingly dissolving the boundary between value-extracting work and self-realizing leisure into “fun playbor,” gamification tries to extract authentic, nonalienated engagement from creative workers without granting actual agency or economic share in exchange (Rey, 2015). In the course, the critical, transformative potential of play is trivialized and domesticated (Trittin, Fiesela, & Maltseva, 2018). This instrumentalization of noninstrumental play is not just paradoxical (Statler et al, 2011): it quickly dries out the well it tries to tap.…”
Section: The Rhetoric Of Choice Architecturementioning
confidence: 99%
“…It also aligns with the rich history of humanistic management from the Hawthorne studies to today’s renaissance (Ferris, 2013; Pirson, 2017), driven by the influx of positive psychology, business ethics, and the global political and moral value shift from economic growth to sustainable well-being (Organization for Economic Co-operation and Development, 2016). This rhetoric acknowledges that to avoid instrumentalization, management has to treat human dignity as its ultimate precondition and end (Pirson, 2017; Trittin, Fieseler, & Maltseva, 2018). As prefigured in McGregor’s Theory-Y management style, it holds that employees (and other stakeholders) will pro-actively act in the organization’s interest if the organization’s goals, work environments, products, and services satisfy their needs for competence, autonomy, or meaning.…”
Section: The Two Futures Of Gamification In Managementmentioning
confidence: 99%